PERILAKU MENYIMPANG YANG “SERING” DILAKUKAN OLEH SISWA KELAS TINGGI SDN 15 JOLLE TAHUN AJARAN 2022/2023 - Sudarto, Sudarto; Muhammad Idris Jafar; Mifta Madaniah (JOEL: Journal of Educational and Language Research, 2023)
The background of this research was that there were several elementary school-age students at SDN 15 Jolle, Lalabata District, Soppeng Regency, who “ofte”n engage in deviant behavior. This research is a survey research that aimed to find out the forms of deviant behavior that were "often" carried out by High Grade students at SDN 15 Jolle, Lalabata District, Soppeng Regency. The population of this study were all the high grade students at SDN 15 Jolle, in totaling 73 students. While the sample used was 30 students. The main instrument in this research was the researcher himself. The supporting instruments used include questionnaires, interview guidelines, and observation sheets. All of these supporting instruments are used to find out and explore the forms of deviant behavior that "often" students do at school. Data analysis includes data reduction, data display and conclusion. The results showed that there were 7 deviant behaviors that "often" were carried out by high grade students at SDN 15 Jolle, namely: arriving late to school, disturbing the friends while studying, taking friends' things without permission, mocking friends, scribbling on desks and chairs in class , leaving school without take a permission from the teacher, and scribbling on the school walls. These deviant behaviors need to be overcome so that they do not continue in the future. This student's deviant behavior can interfere with the teaching-learning process at school